2013
DOI: 10.1105/tpc.113.115063
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Receptor DA1 Interacts with the E3 Ubiquitin Ligase DA2 to Regulate Seed and Organ Size in Arabidopsis

Abstract: ORCID ID: 0000-0002-0025-4444 (Y.L.).Seed size in higher plants is determined by the coordinated growth of the embryo, endosperm, and maternal tissue. Several factors that act maternally to regulate seed size have been identified, such as AUXIN RESPONSE FACTOR2, APETALA2, KLUH, and DA1, but the genetic and molecular mechanisms of these factors in seed size control are almost totally unknown. We previously demonstrated that the ubiquitin receptor DA1 acts synergistically with the E3 ubiquitin ligase ENHANCER1 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
313
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(322 citation statements)
references
References 50 publications
8
313
1
Order By: Relevance
“…These data indicated that BB may influence leaf final size at earlier stages of growth than DA1. We demonstrated previously that DA1 and DA2 physically interact (Xia et al 2013). Pull-down experiments showed that GST-tagged DA1 also interacted with HIS-tagged BB but not with HIStagged BBR (BB-related; At3g19910), a close homolog of BB ( Fig.…”
Section: Genetic and Physical Interactions Of Da1 Bb And Da2mentioning
confidence: 72%
See 3 more Smart Citations
“…These data indicated that BB may influence leaf final size at earlier stages of growth than DA1. We demonstrated previously that DA1 and DA2 physically interact (Xia et al 2013). Pull-down experiments showed that GST-tagged DA1 also interacted with HIS-tagged BB but not with HIStagged BBR (BB-related; At3g19910), a close homolog of BB ( Fig.…”
Section: Genetic and Physical Interactions Of Da1 Bb And Da2mentioning
confidence: 72%
“…We previously identified genetic interactions between the da1-1 allele of DA1 and genes encoding the RING E3 ligases BB (Li et al 2008) and DA2 (Xia et al 2013) that led to synergistic increases in seed and organ sizes. In this study, we used the da1-1-enhancing allele of BB called eod1-2 (Li et al 2008) and refer to the mutant version as bbeod1-2 and the wild-type version as BB.…”
Section: Genetic and Physical Interactions Of Da1 Bb And Da2mentioning
confidence: 99%
See 2 more Smart Citations
“…DA2 447 and enhancer of DA1 (EOD1) encode proteins with E3 448 ubiquitin ligase activity and are also negative regulators of 449 seed size, as shown by the enlarged seeds of single mutants 450 da2-1 and eod1. They may act synergistically with DA1,as 451 observed by the enhanced seed size of da1-1 da2-1 and 452 da1-1 eod1 double mutants in comparison with da1 mutant 453 (Xia et al 2013). EOD3 encodes cytochrome P450 454 CYP78A6.…”
Section: U N C O R R E C T E D P R O O F 431mentioning
confidence: 95%